A low dielectric constant flexible polyimide composite material and preparation method thereof

By designing block polymerized macromolecular diamine monomer and chemical crosslinking technology, the dielectric constant of polyimide materials is reduced, and the problems of high dielectric constant and reduced water resistance of the material are solved, and polyimide composite materials with low dielectric constant, strong water resistance and excellent mechanical properties are realized.

CN118684887BActive Publication Date: 2025-03-28ZHEJIANG JUDING NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410828289.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-03-28
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The dielectric constant of polyimide materials is high, which is difficult to meet the requirements of some electronic devices for low dielectric constant. At the same time, the introduction of fluorine elements or the construction of porous structures will affect the water resistance and mechanical properties of the material.

Method used

By designing block polymerized macromolecular diamine monomers containing tert-butyl and trifluorotoluene, it participates in the synthesis process of polyimides, forming a polyimide molecular chain containing a large amount of fluorine elements, and chemical crosslinking of hollow glass microbeads and polyimide matrix is ​​achieved through chemical bond connection.

Benefits of technology

It realizes the low dielectric constant, good water resistance and mechanical properties of polyimide materials, and is suitable for the electronics field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118684887B_ABST
    Figure CN118684887B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of materials, and discloses a low dielectric constant flexible polyimide composite material and a preparation method thereof. By designing the diamine monomer of polyimide, a block polymer macromolecule containing tert-butyl and trifluorotoluene is prepared as the diamine monomer, and the block polymer macromolecule is involved in the synthesis process of polyimide, so that the formed polyimide molecular chain contains a large amount of fluorine elements, which is beneficial to reduce the dielectric constant of the polyimide material. In addition, the presence of a large number of tert-butyl segments can make the polyimide material show extremely strong hydrophobicity. At the same time, the present invention adopts a chemical bond connection method to achieve chemical crosslinking of hollow glass microspheres and polyimide matrix, so that the hollow glass microspheres can effectively play their own advantages as inorganic materials in the form of chemical crosslinking points, and improve the mechanical properties of the polyimide material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a low dielectric constant flexible polyimide composite material and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, the performance requirements for electronic components are getting higher and higher. Especially in the fields of high-frequency circuits, microwave circuits and 5G communications, the importance of low dielectric constant materials has become increasingly prominent. Polyimide is a polymer material with excellent thermal stability, mechanical properties, chemical stability and flexibility. Its molecular chain contains a large number of aromatic ring structures, which gives it excellent high temperature resistance. The decomposition temperature is generally over 500°C. It is one of the most thermally stable organic polymers known. At the same time, polyimide materials also have good mechanical properties, such as high elastic modulus, high strength, excellent wear resistance, chemical stability and radiation resistance. It can maintain stable performance in various harsh environments. Therefore, it has a wide range of application prospects in the field of electronics.

[0003] Although polyimide has excellent performance in all aspects, its dielectric constant is relatively high, about 3.5, which is difficult to meet the requirements of some electronic devices for low dielectric constants. Therefore, it is urgent to reduce the dielectric constant of polyimide. The common methods at present mainly introduce fluorine elements into the polyimide molecular chain to reduce the molar polarization, or by constructing a pore structure in the polyimide to reduce the dielectric constant of polyimide. However, the introduction of fluorine elements will cause the water resistance of polyimide materials to decrease, and the construction of a large number of pore structures will have an impact on the mechanical strength of polyimide materials, which is actually not conducive to the practical application of polyimide.

[0004] Based on this, the present invention provides a flexible polyimide composite material, which not only has a low dielectric constant, but also has strong water resistance and good mechanical properties, and can be directly used in the electronic field. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a low dielectric constant flexible polyimide composite material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a low dielectric constant flexible polyimide composite material comprises the following steps:

[0008] The first step is to add the diamine monomer and the dianhydride monomer into N,N-dimethylformamide, stir mechanically, fill with nitrogen as a protective gas, and react for 1-3 hours under continuous stirring to obtain a precursor solution;

[0009] Step 2: Add the modified hollow glass microspheres to the precursor solution at a solid-liquid ratio of 1-3 g: 80-100 mL, perform ultrasonic dispersion for 20-30 min, and prepare a dispersion with a solid content of 3-5%. Continue to add a phase transfer catalyst to the dispersion, control the temperature at 60-70 ° C, keep stirring for 2-4 hours, and discharge the material to obtain a polyimide composite slurry;

[0010] The third step is to let the polyimide composite slurry stand for 20-40 minutes to remove bubbles, and then evenly coat it on the surface of the substrate. Then, place the entire substrate in a vacuum drying oven and start the heating program for thermal imidization. Then, take it out and peel off the substrate to obtain a flexible polyimide composite material.

[0011] Specifically, equimolar amounts of diamine monomers and dianhydride monomers are stirred and mixed at room temperature and interact with each other to form a polyamic acid solution. Under the action of a phase transfer catalyst, the modified hollow glass microspheres can undergo ring-opening esterification with the active carboxyl groups in the polyamic acid structure, thereby achieving a composite of the hollow glass microspheres and the polyamic acid in the form of chemical bonds to obtain a polyimide composite slurry. Finally, the slurry is coated on the surface of a substrate and thermal imidization is performed to obtain a flexible composite film material of hollow glass microspheres-polyimide, namely, a flexible polyimide composite material.

[0012] A low dielectric constant flexible polyimide composite material is prepared by adopting the preparation method.

[0013] As a further embodiment of the present invention, in the first step, the preparation method of the diamine monomer is as follows:

[0014] Add tert-butyl glycol monomer and toluene to a polymerization kettle filled with nitrogen, start stirring, and after forming a uniform reaction liquid, add alkaline hydroxide solution, stir at 50-60°C for 1-2 hours, then add 3,5-dibromotrifluorotoluene to the polymerization kettle. After the addition, increase the temperature to 70-80°C, continue to keep warm and stir for 2-4 hours, then add the end-capping agent 2-chloroethylamine hydrochloride to the polymerization kettle, after the addition, keep warm for 30-60 minutes, evaporate the solvent, cool and discharge the material to obtain a diamine monomer.

[0015] Specifically, alkaline hydroxide is first used to activate the active substituted hydroxyl group in the tert-butyl diol monomer, and then 3,5-dibromotrifluorotoluene is added as a linker to cause an uninterrupted substitution reaction under high temperature conditions to form a block polymerized macromolecular diamine monomer containing tert-butyl and trifluorotoluene.

[0016] As a further embodiment of the present invention, the tert-butyl diol monomer is selected from 3,3-dimethylbutane-1,2-diol or tert-butyl diethanolamine.

[0017] As a further embodiment of the present invention, the molar ratio of the tert-butyl glycol monomer to 3,5-dibromotrifluorotoluene is 1:0.8-0.9.

[0018] As a further embodiment of the present invention, in the first step, the dianhydride monomer is selected from any one of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,3',6,7'-naphthalenetetracarboxylic anhydride, 2,3',3,4'-biphenyltetracarboxylic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride or 4,4'-oxydiphthalic anhydride.

[0019] As a further solution of the present invention, in the second step, the modified hollow glass microspheres are prepared by using a catalyst to catalyze epoxidized soybean oil to modify the surface of the hollow glass microspheres.

[0020] As a further embodiment of the present invention, the catalyst is stannous chloride.

[0021] Specifically, the surface of the hollow glass microspheres contains silanol groups, which can undergo ring-opening addition with the epoxy groups of the epoxidized soybean oil under the catalytic action of stannous chloride, thereby realizing the surface modification of the hollow glass microspheres by the epoxidized soybean oil. Since the structure of the epoxidized soybean oil contains multiple epoxy substituents, a large number of epoxy groups can be introduced into the surface of the hollow glass microspheres to prepare modified hollow glass microspheres.

[0022] As a further embodiment of the present invention, in the second step, the phase transfer catalyst is any one of N,N-dimethylbenzylamine, tetrabutylammonium hydrogen sulfate, tetrabutylammonium chloride or tetrabutylammonium bromide.

[0023] As a further solution of the present invention, in the third step, the heating program is to keep warm at 150°C, 250°C, and 320°C for 1 hour respectively.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention designs the diamine monomer of polyimide to prepare a block polymer macromolecule containing tert-butyl and trifluorotoluene as the diamine monomer, which participates in the synthesis process of polyimide, so that the formed polyimide molecular chain contains a large amount of fluorine element, which is beneficial to reduce the dielectric constant of the polyimide material. In addition, the presence of a large number of tert-butyl chain segments can make the polyimide material exhibit extremely strong hydrophobicity, thereby improving the problem of reduced water resistance of the polyimide material due to the introduction of fluorine element.

[0026] (2) Since the designed diamine monomer is a polymeric structure, the content of imide heterocycles in the obtained polyimide molecular chain is reduced, which affects its mechanical properties. Therefore, the present invention adopts a chemical bond connection method to achieve chemical crosslinking of hollow glass microspheres and polyimide matrix, so that the hollow glass microspheres can effectively play their advantages as inorganic materials in the form of chemical crosslinking points, thereby improving the mechanical properties of polyimide materials. In addition, the uniform dispersion of hollow glass microspheres can also introduce a hollow structure into the polyimide material, thereby further reducing the dielectric constant of the polyimide material.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 This is an infrared test image of the diamine monomer in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] Preparation of diamine monomers

[0033] Add 0.5 g of tert-butyldiethanolamine and toluene to a polymerization kettle filled with nitrogen, start stirring, and after forming a uniform reaction liquid, add 5 mL of a 25% by mass sodium hydroxide solution, stir at 55° C. for 2 h, then add 0.8 g of 3,5-dibromotrifluorotoluene to the polymerization kettle. After the addition, increase the temperature to 75° C., continue to keep warm and stir for 3 h, then add 0.2 g of 2-chloroethylamine hydrochloride as a capping agent to the polymerization kettle, keep warm for 40 min, evaporate the solvent, cool and discharge, and obtain a diamine monomer.

[0034] Figure 1 This is the infrared test image of the diamine monomer, where 3369cm -1 and 3298cm -1The absorption peak at 3000 cm-1 is the NH stretching vibration absorption peak of the amine group. -1 ~3100cm -1 The absorption peak at 1383 cm is the characteristic absorption peak of carbon and hydrogen in the benzene ring skeleton. -1 The absorption peak at 1105cm is the characteristic absorption peak of CF. -1 The absorption peak that appears at is the CO characteristic absorption peak of the ether bond.

[0035] Example 2

[0036] Preparation of modified hollow glass microspheres

[0037] 4.5 g of hollow glass microspheres with an average particle size of 5 μm were dispersed in toluene, and then 2.6 g of epoxy soybean oil and 0.1 g of stannous chloride were added to the obtained dispersion. After the addition, the mixture was mixed by mechanical stirring, and the heating was turned on. Under stirring conditions, the mixture was kept at 65° C. for 4 h, and the temperature was lowered and the mixture was discharged. The solid product was collected by centrifugation, and washed and dried to obtain modified hollow glass microspheres.

[0038] Using the hydrochloric acid acetone method, 0.1 g of the modified hollow glass microspheres were taken as samples for epoxy value determination. The test results showed that the epoxy value of the modified hollow glass microspheres was 5.811 mmol / g.

[0039] Example 3

[0040] Preparation of flexible polyimide composites

[0041] The first step is to add 1.5 g of the diamine monomer prepared in Example 1 and 0.4 g of 2,3',3,4'-biphenyltetracarboxylic dianhydride to 50 mL of N,N-dimethylformamide, stir mechanically, fill with nitrogen as a protective gas, and react for 2 h under continuous stirring to obtain a precursor solution;

[0042] Step 2: Add 1 g of the modified hollow glass microspheres prepared in Example 2 to 80 mL of the precursor solution, perform ultrasonic dispersion for 30 min, continue to add 0.1 g of tetrabutylammonium hydrogen sulfate to the dispersion, control the temperature at 65° C., keep stirring for 3 h, and discharge the material to obtain a polyimide composite slurry;

[0043] The third step is to let the polyimide composite slurry stand for 30 minutes to remove bubbles, and then evenly coat it on the surface of the substrate. Then, place the entire substrate in a vacuum drying oven and start the heating program. Keep it warm at 150°C, 250°C, and 320°C for 1 hour respectively. After thermal imidization, take it out and peel off the substrate to obtain a flexible polyimide composite material.

[0044] Example 4

[0045] Preparation of flexible polyimide composites

[0046] The first step is to add 1.5 g of the diamine monomer prepared in Example 1 and 0.4 g of 2,3',3,4'-biphenyltetracarboxylic dianhydride to 50 mL of N,N-dimethylformamide, stir mechanically, fill with nitrogen as a protective gas, and react for 2 h under continuous stirring to obtain a precursor solution;

[0047] Step 2: Add 2 g of the modified hollow glass microspheres prepared in Example 2 to 95 mL of the precursor solution, perform ultrasonic dispersion for 30 min, continue to add 0.1 g of tetrabutylammonium bromide to the dispersion, control the temperature at 65° C., keep stirring for 3 h, and discharge the material to obtain a polyimide composite slurry;

[0048] The third step is to let the polyimide composite slurry stand for 30 minutes to remove bubbles, and then evenly coat it on the surface of the substrate. Then, place the entire substrate in a vacuum drying oven and start the heating program at 150°C, 250°C, and 320°C for 1 hour. After thermal imidization, take it out and peel off the substrate to obtain a flexible polyimide composite material.

[0049] Example 5

[0050] Preparation of flexible polyimide composites

[0051] The first step is to add 1.5 g of the diamine monomer prepared in Example 1 and 0.4 g of 2,3',3,4'-biphenyltetracarboxylic dianhydride to 50 mL of N,N-dimethylformamide, stir mechanically, fill with nitrogen as a protective gas, and react for 2 h under continuous stirring to obtain a precursor solution;

[0052] Step 2: Add 1 g of the modified hollow glass microspheres prepared in Example 2 to 100 mL of the precursor solution, perform ultrasonic dispersion for 30 min, continue to add 0.1 g of tetrabutylammonium chloride to the dispersion, control the temperature at 65° C., keep stirring for 3 h, and discharge the material to obtain a polyimide composite slurry;

[0053] The third step is to let the polyimide composite slurry stand for 40 minutes to remove bubbles, and then evenly coat it on the surface of the substrate. Then, place the entire substrate in a vacuum drying oven and start the heating program to keep it warm at 150°C, 250°C, and 320°C for 1 hour. After thermal imidization, take it out and peel off the substrate to obtain a flexible polyimide composite material.

[0054] Comparative Example 1

[0055] The preparation process of the flexible polyimide composite material in this comparative example is different from that in Example 4 in that the diamine monomer is replaced with 4,4-diaminodiphenyl ether, and the other conditions remain unchanged.

[0056] Comparative Example 2

[0057] The preparation process of the flexible polyimide composite material in this comparative example is different from that in Example 4 in that the precursor solution obtained in the first step is directly coated on the surface of the substrate for thermal imidization, and the other steps remain unchanged.

[0058] Test Case

[0059] The flexible polyimide composite materials in Examples 3 to 5 and Comparative Examples 1 to 2 were made into test samples, and the following performance tests were performed:

[0060] a. Use WK65120B high-precision impedance analyzer to test the dielectric constant of the sample;

[0061] b. Use XWW-20A universal testing machine to test the tensile strength of the sample;

[0062] c. Weigh the sample and record the weight as X. Then immerse the sample in purified water and keep it at 80℃ for 12 hours. Then take it out and wipe off the moisture on the surface of the sample. Weigh it again and record it as Y. Use the formula [(YX) / X]×100% to calculate the water absorption rate of the sample and evaluate the water resistance of the sample.

[0063] The results of the above tests are shown in the following table:

[0064] project Dielectric constant Tensile strength / MPa Water absorption / % Example 3 2.51 138.4 0.8 Example 4 2.49 139.1 0.7 Example 5 2.49 138.7 0.8 Comparative Example 1 2.80 138.5 2.1 Comparative Example 2 3.17 79.8 0.9

[0065] Analysis of the test results in the above table shows that the diamine monomer prepared in Example 1 of the present invention is used in combination with modified hollow glass microspheres to prepare a polyimide composite material with a low dielectric constant, excellent mechanical properties and good water resistance, which can be used in the field of electronic products.

[0066] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0067] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a low dielectric constant flexible polyimide composite material, characterized in that: The following steps are involved: The first step is to add the diamine monomer and the dianhydride monomer into N,N-dimethylformamide, stir mechanically, fill with nitrogen as a protective gas, and react for 1-3 hours under continuous stirring to obtain a precursor solution; Step 2: Add the modified hollow glass microspheres to the precursor solution at a solid-liquid ratio of 1-3 g: 80-100 mL, perform ultrasonic dispersion for 20-30 min, continue to add a phase transfer catalyst to the dispersion, control the temperature at 60-70 ° C, keep stirring for 2-4 h, and discharge the material to obtain a polyimide composite slurry; The third step is to let the polyimide composite slurry stand for 20-40 minutes to remove bubbles, and then evenly coat it on the surface of the substrate. Then, the substrate is placed in a vacuum drying oven as a whole, and the heating program is turned on for thermal imidization. Then, the substrate is taken out and peeled off to obtain a flexible polyimide composite material. The preparation method of the diamine monomer is as follows: Add tert-butyl glycol monomer and toluene to a polymerization kettle filled with nitrogen, start stirring, and after forming a uniform reaction liquid, add a sodium hydroxide solution with a mass fraction of 15-25%, stir at 50-60° C. for 1-2 hours, then add 3,5-dibromotrifluorotoluene to the polymerization kettle, after adding, increase the temperature to 70-80° C., continue to keep warm and stir for 2-4 hours, then add a blocking agent 2-chloroethylamine hydrochloride to the polymerization kettle, after adding, keep warm for 30-60 minutes, evaporate the solvent, cool down and discharge, and obtain a diamine monomer; The modified hollow glass microspheres are prepared by using a catalyst to catalyze epoxy soybean oil to modify the surface of the hollow glass microspheres.

2. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: The tert-butyl diol monomer is selected from 3,3-dimethylbutane-1,2-diol or tert-butyl diethanolamine.

3. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: The molar ratio of the tert-butyl glycol monomer to 3,5-dibromotrifluorotoluene is 1:0.8-0.

9.

4. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: In the first step, the dianhydride monomer is selected from any one of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,3',6,7'-naphthalenetetracarboxylic anhydride, 2,3',3,4'-biphenyltetracarboxylic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride or 4,4'-oxydiphthalic anhydride.

5. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: The catalyst is stannous chloride.

6. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: In the second step, the phase transfer catalyst is any one of N,N-dimethylbenzylamine, tetrabutylammonium hydrogen sulfate, tetrabutylammonium chloride or tetrabutylammonium bromide.

7. The method for preparing a low dielectric constant flexible polyimide composite material according to claim 1, characterized in that: In the third step, the heating program is to keep the temperature at 150° C., 250° C., and 320° C. for 1 h respectively.

8. A low dielectric constant flexible polyimide composite material, characterized in that: The method is prepared according to claim 1.

Citation Information

Patent Citations

  • Heat insulation composite film and preparation method thereof

    CN106751823A

  • Low-dielectric-constant polyimide film and preparation method thereof

    CN112679770A